Optical Characterization of a Pendular Impact - Saldaña-Heredia, Alonso; Martínez-Calzada, Víctor; Márquez-Aguilar, Pedro Antonio; Hernández-Cruz, Daniel (Frontiers in Physics, 2020)
We present a simple but accurate correlation between an experimental characterization and a simple analytical prediction of a wave propagation induced by the impact of a pendulum in a box filled with fine sand; this research is based on optical measurements and was carried out using the digital image correlation technique to determine the motion on the surface of the box visually observed by the reflection of the laser. We suggest that the reaction to the impact in the body will be similar to an equivalent damped mass-spring system, obtaining an average error of 3.67208 x10^-4.